Near-tip strain evolution under cyclic loading: In situ experimental observation and numerical modelling. (February 2015) - Tong, J.; Lin, B.; Lu, Y.-W.; Madi, K.; Tai, Y.H.; Yates, J.R.; Doquet, V.
Highlights: Near-tip normal strain ratchetting is captured in situ at peak loads for the first time. Stereo-DIC and SEM-DIC were used to monitor normal strain evolution with cycles. Normal strains at distances from 6 to 60 μm to the crack tip were monitored. Strain ratchetting is more evident close to the crack tip and under higher loads. 3D FE models are able to reproduce results from the Stereo-DIC measurements. Abstract: The concept of ratchetting strain as a crack driving force in controlling crack growth has previously been explored at Portsmouth using numerical approaches for nickel-based superalloys. In this paper, we report the first quantitative experimental evidence of near-tip strain ratchetting with cycles, as captured in situ by digital image correlation (DIC) technique on a compact tension specimen of stainless steel 316L, using both Stereo and SEM systems. The evolution of the near-tip strains with loading cycles was monitored whilst the crack tip was kept stationary. The strains normal to the crack plane were examined over selected distances from 6 to 57 μm to the crack tip for a number of cycles. The results show that strain ratchetting occurs with loading cycles, and is particularly evident close to the crack tip and under higher loads. 3D finite element models have also been developed to simulate the experiments and the results from the simulation are compared with those from the DIC measurements. This is the first time that near-tip strain ratchetting has been captured in situ at the peak loads during cyclic loading.